Nitric oxide synthase 3 and endothelin 1 immunoreactivity in pulmonary hypertension - Gupta Rajib; Vaideeswar Pradeep (Wolters Kluwer Medknow Publications, 2010)
Context: Pulmonary hypertension (PH) is a serious and sometimes life-threatening event that occurs as a complication of various cardiopulmonary disorders, of which rheumatic heart disease (RHD) is an important example in our country. The pathogenesis of PH is a complex, multistep process in which "pulmonary endothelial dysfunction" (PED) is widely regarded as the central pathogenetic event. PED is, in turn, influenced by several local and systemic factors, of which nitric oxide synthase 3 (NOS3) and endothelin 1 (ET1) are 2 prime candidates, and are the subject of our study. Aims: Our aim was to study the immunoreactivity of NOS3 and ET1 in the pulmonary vasculature of PH patients of various etiologies, with emphasis on RHD cases. Settings and Design: A retrospective, autopsy-based study. Subjects and Methods: A total of 49 autopsy cases (39 patients and 10 controls) were chosen for our study. Of the 39 patients, 20 had PH secondary to RHD, whereas the remaining 19 patients had non-RHD etiologies as the basis of their PH. Lung sections taken from all the 49 cases were subjected to routine H and E, elastic van Gieson, and immunohistochemical staining (with NOS3 and ET1 separately). The intensity of immunostaining in all the cases and controls were then graded as focal/diffuse and weak/strong. Results: Controls showed positivity for both NOS3 (bronchiolar epithelium) and ET1 (endothelium of pulmonary arteries). Characteristic changes of PH on H and E were seen in 14 out of 19 non-RHD cases, which matched with the number of ET1 positivity cases. Similarly, for the RHD cases, 14 out of 20 cases showed changes of PH on H and E, but only 2 cases showed mild, focal positivity for ET1. Surprisingly, NOS3 positivity was largely absent in both the non-RHD and RHD cases. Conclusions: Our study showed NOS3 negativity and ET1 positivity in the lung vasculature of patients with PH, a conclusion more or less in line with the predominant view of the other investigators in this field. But at the same time, our study could not conclude an unequivocal role of NOS3 in PH, whereas it could, in the case of ET1.